Studi Pendahuluan Pengembangan E-Modul IPA Materi Energi Terbarukan Pada Kurikulum Program Sekolah Penggerak - Anisa Triwijaya; Asrizal Asrizal; Hidayati Hidayati; Renol Afrizon (PAKAR Pendidikan, 2023)
21st-century skills must be built, especially in creative thinking, critical thinking, communication, and collaboration. The concept of independent learning present in 2021 is a form of developing and strengthening Indonesian national character. According to the Pancasila learning profile, the driving school program curriculum aims to develop and strengthen competencies and characters. The research analyzes learning problems, student characteristics, learning objectives, and settings. This type of research is descriptive research, a preliminary study that refers to the preliminary research stage in the Plomp development model. The population in this study were students of class X SMAN 2 and 9 Padang who implemented the driving school curriculum. From the data analysis that has been done, it can be stated that there are four research results. First, the problems teachers face are learning objectives in the moderate category, learning methods in the moderate category, learning materials in the strong category, teaching materials in the moderate category, and learning evaluation in the moderate category. Second, student characteristics, namely learning motivation, learning style, learning interest, and attitude, are in a strong category. Third, the analysis of learning objectives shows that competence has a suitable category, content is a good category, variety a suitable category, and KKO a good category. Fourth, the analysis of learning arrangements shows that the learning arrangements designed by teachers are quite different from the expected ideal conditions.